Diagenetic alteration of the structure and δ18O signature of Palaeozoic fish and conodont apatite: Potential use for corrected isotope signatures in palaeoenvironmental interpretation - Barham, Milo; Joachimski, M.; Murray, J.; Williams, D. (Elsevier Science BV, 2012)
The oxygen isotopic compositions of Carboniferous conodonts and fish microfossils (ichthyoliths), from identical samples, were analysed in tandem in order to test whether these phosphatic media can be reliably used for palaeoclimatic reconstruction. The structure of conodonts and of most ichthyoliths analysed are somewhat analogous to the enamel and dentine/bone tissue, respectively, of modern mammals. Therefore, the diagenetic susceptibilities of the taxa analysed may provide important clues to other palaeoclimatic studies utilising a variety of biogenic apatite.Thermal maturation indices and scanning electron microscopy were used to characterise the preservation of biogenic apatite. Despite a high conodont colour alteration index (CAI) of ~5.5, conodont elements appear to have been only mildly affected by diagenetic alteration. In contrast, ichthyoliths were commonly recrystallised and exhibited diagenetic apatitic overgrowths containing amorphous pyrolytic carbon, interpreted as indicating that at least some overgrowth material derived from the original biogenic apatite.Diagenetic alteration has resulted in ichthyolith d18O values being systematically lower by, on average, 2.9‰ (1s = ±0.3) relative to conodont apatite. Conodont samples yielded regionally correlatable isotope values, which can be interpreted in terms of more palaeoenvironmentally sensible palaeotemperatures relative to ichthyolith values. Densely crystalline, enamel-like conodont elements are interpreted as the more robust phosphatic medium to preserve original isotopic compositions. The strong correlation (r = 0.8) of the d18O values of the more structurally pristine conodont and commonly recrystallised ichthyolith apatite, indicates that (i) despite diagenetic lowering of absolute isotope values, original palaeoenvironmental records may be preserved and (ii) diagenetic overprinting may result in a stable offset, and therefore be correctable, locally.